The Relationship between Food Safety Knowledge and Optimistic Bias among Food Handlers in The State High School Canteens in Magelang City, Indonesia - Sekarsari, Kivani Amalia; Budiningsari, Dwi; Yeni Prawiningdyah (BKM Public Health and Community Medicine, 2024)
Purpose: This study is to find out the relationship between food safety knowledge and optimistic bias in food handlers in the canteens of five State High School, Magelang City, Indonesia. Method: The research was conducted in an analytical observational with a cross sectional design. This study involved 41 food handlers at the canteens of five State High School, Magelang City, Indonesia, who were determined using total sampling techniques. The independent variable was food safety knowledge and the dependent variable was optimistic bias. A validated questionnaire on food safety knowledge and optimistic bias was used. The categories of food safety knowledge variable consist of good (score ≥ 70) and poor (score < 70) food safety knowledge. Meanwhile, the categories of variable optimistic bias consist of high (score < 24), possible (score = 24), and low (score > 24) optimistic bias. The Spearman correlation test was conducted. Result: First, food handlers have good food safety knowledge with a score of 71,54 out of 100. Second, food handlers have high optimistic bias with a score of 8,073 out of 42. Third, there are no significant relationship between age, education level, food safety information, and work experience with food safety knowledge. Fourth, there is a significant relationship between age and optimistic bias with a value of p = 0,043 and r = -0,317. Fifth, there is no significant relationship between food safety knowledge and optimistic bias (p = 0,704 and r 0,061). Conclusion: There is no significant relationship between food safety knowledge and optimistic bias among food handlers in five State High School canteens, Magelang City, Indonesia. School canteen is an important service for students, so food safety training supervised by the public health center and health department also feedback from students is needed to improve the quality of the service.